FUNGSI DAN MAKNA KUE CANG DALAM FESTIVAL DUAN WU JIE MASYARAKAT ETNIS TIONGHOA DI KOTA MEDAN - Lisa Wulandari Nasution (Haluan Sastra Budaya, 2022)
The title of this research is the Function and Meaning of Cang Cake in the Duan Wu Jie Festival of Chinese Ethnic Communities in Medan. This study aims to explain how the process of welcoming Cang Cake in the Duan Wu Jie Festival of the Chinese ethnic community in Medan City, and to explain how the function and meaning of Cang Cake in the Duan Wu Jie Festival of the Chinese ethnic community in Medan City. The method used in this study is qualitative methods. Some of the analysis results obtained from this research are Cang Cake is a traditional food of the Chinese ethnic community, cang cake is very popular in Indonesia, Java Island to Sumatra, especially in Medan City. Cang cake made from glutinous rice. Cang cakes have types that are filled and some are not. Cang cakes that contain the name bakcang which means pork, while cang cakes that do not contain are named kicang. The research uses the Functionalism Theory which this theory applies in culture regarding the habits in the life institutions of the Chinese ethnic community towards their culture.